2001
DOI: 10.1212/wnl.57.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in children with gelastic seizures and hypothalamic hamartoma

Abstract: These findings are consistent with cognitive functions and affective/emotional states associated with conduction pathways of the hypothalamus involving cortical association areas and amygdala and hippocampal formation. These abnormalities can account for the prominent deficit found in integrating information in the processing of memories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 15 publications
7
74
2
2
Order By: Relevance
“…10,23,24,43,70 Tassinari and colleagues 106 published an extensive review of patients with gelastic seizures in which they reported on 60 patients with gelastic seizures without the presence of HH, suggesting that ictal laughter is not necessarily pathognomonic for HH. In fact, gelastic seizures may also be present in frontal and temporal lobe epilepsies.…”
Section: Epileptic Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…10,23,24,43,70 Tassinari and colleagues 106 published an extensive review of patients with gelastic seizures in which they reported on 60 patients with gelastic seizures without the presence of HH, suggesting that ictal laughter is not necessarily pathognomonic for HH. In fact, gelastic seizures may also be present in frontal and temporal lobe epilepsies.…”
Section: Epileptic Syndromesmentioning
confidence: 99%
“…2 In addition to delinquency and aggressive outbursts, a slowly progressive decline in cognitive functioning has also been frequently observed in patients with HH-related gelastic seizures. 6,10,14,43,78 The decline of behavior and cognitive function typically parallels the exacerbation of the seizure disorder. Quiske et al 91 published the first in-depth report on cognitive performance in adult and juvenile patients with gelastic seizures and HH, in which they found cognitive impairments in more than half of their patients.…”
Section: Behavioral and Cognitive Disordersmentioning
confidence: 99%
“…4,51,55) Developmental delays correlate with the severity, frequency, and variety of the seizure patterns. 8,25,55) Of all reported patients with HH, 49% manifested cognitive disturbance and 31% had behavioral problems; all of them had seizures. 51) The behavioral problems have been described as restlessness, violence including severe rage attacks, emotional instability, obsession, autism, and anti-social behavior.…”
Section: Cognitive Dysfunction and Behavioral Problemsmentioning
confidence: 99%
“…26) Recurrent excitatory damage produced by the spreading of seizure activity from the HH through the mammillothalamic pathway and associated brain area may cause the progressive cognitive deterioration in patients with HH. 25) …”
Section: Underlying Pathophysiology Of Symptoms I Seizuresmentioning
confidence: 99%
“…Owing to significant, but partial, efficacy 25 patients (62.5 %) were treated twice. The preoperative cognitive deficits, behavioral disturbances, and investigated relationship of seizure severity and anatomical type to cognitive abilities were characterized [71,72]. Low peripheral doses were used because of the close relationship with optic pathways and hypothalamus (median 17 Gy; range 13-26 Gy).…”
Section: Epilepsymentioning
confidence: 99%